Rancang Bangun Alat Pengusir Tikus Dan Burung Pada Tanaman Padi Berbasis Tenaga Surya - Bana, Muhammad Sulton; Rahmawati, Diana; Joni, Koko; Ulum, Miftachul (Universitas Hang Tuah, 2020)
Rice is the staple food of the Indonesian population. The main commodity of rice production is rice farmers. At present many rice farmers complain that rice yields are less than optimal, this is due to the many attacks of rice pests, especially rats and birds. To overcome these pests, farmers usually use rat poison, mouse burners and wires that are electrified which are placed around the rice fields, it is certainly very dangerous and very impacting on the rice field ecosystem. With the development of advanced technology now it is possible to build a system that is able to anticipate and minimize rice pest attacks. One of them is using ultrasonic waves as a mouse repellent and the movement of a scarecrow as a bird repellent. Because mice have sensitive hearing abilities so they feel disturbed when they hear the sound of ultrasonic waves with a certain frequency. Likewise birds, rice-eating birds will feel disturbed when there is a sudden movement around it. The objective to be achieved in this research is to facilitate the work of farmers to maintain their fields and also to maximize rice yields